ANALISIS PENGARUH PERSEPSI NASABAH TERHADAP PENGGUNAAN INTERNET BANKING - NUNING VERDINA (JURNAL ILMIAH MAKSITEK, 2021)
The use of Internet Banking is a service provided by banks to improve the efficiency of banking operations. This researchwas conducted with the aim to analyze the Effect of Benefit Perception, Ease of Use, Trust, Risk, and Service Features oninternet banking usage. The results of this research are expected to contribute to banking in order to increase credibility andcontinue to improve better service for customers. This study used questionnaires as instruments to take samples of 125respondents, who were users of Internet Banking Bank Mestika Operational Headquarters in Medan, with purpsive samplingtechniques. The study used multiple linear regression analysis methods. The results showed that partially the perception ofbenefits, ease of use, and service features had a significant effect on the use of Internet Banking, while the perception oftrust and risk had no significant effect on the use of Internet Banking. While simultaneously the perception of benefits, easeof use, trust, risk and service features significantly affect the use of Internet Banking with a significance value of 0.000 <0.05. The variable ability to explain Internet Banking usage was 61.4%, while the remaining 38.6% was influenced by otherfactors not included in the study. In future research, it is expected to use more diverse free variables in predicting their effecton bound variables in order to obtain more specific results.